کُردی ءُ بلوچی ءِ لہتیں ھوریں گالواری دروشم: Few Similarities dialectical formats of Balochi and Kurdish - Buzdar, Wahid Bakhsh (Hanken, 2013)
Balochi and Kurdi both belong to the northwestern branch of the Iranian language family and share a lot of similarities in context of syntical, morphological and lexical for thousands of years. This paper illustrates the lexical and etymological similarities between the Kurdish and Balochi languages.